As rodas de leitura em prisões e seus processos educativos - Portela, Gustavo Aranha (Universidade Federal de São Carlos, 2020)
The following study analyzes the educational processes which happen in Rodas de Leitura in a correctional facility in the state of São Paulo, Brazil. Our interest for the subject has arrived from our participation through unscholarly activities, in some correctional facilities, where we could notice that the gatherings taking place were spaces for personal improvement, exchange experiences, places for people to unburden themselves and that can change ways of thinking, perceiving and forge opinions. Driven by those experiences, we have built our research object: Which educational processes can the social practice Roda de Leitura develop in a space of deprivation of liberty? Guided by this question, we have defined our general goal: to present the educational processes which flow from the social practice of Roda de Leitura that happens in a correctional facility in the state of São Paulo. It is a research of qualitative nature and the data collection was done based on the principle of participating observation. The observation, the informal conversations and the gatherings which happen in Roda de Leitura were used to gather data which were organized in Field Journals. Questionnaires were applied to the collaborators with the goal of characterizing the group and exposing their perceptions about the Roda de Leitura and its educational processes. The data were organized, and four analysis focuses were determined: The meaning of Roda de Leitura, The contributions from Roda de Leitura to the school, The mediator role of Roda de Leitura, The organization of Roda de Leitura in the collaborator’s perspective. The analysis has shown that the Roda de Leitura allows the people to have pleasant dialogues, to interact amongst themselves, to disagree, agree and to partake in the construction of new knowledge. The analysis also shows that the mediator as an emancipating educator promotes situations for identity formation, self-esteem and self-reliance. The participants show themselves eager to keep having the Rodas, suggest other ways of doing them and show solidarity to the other people who inhabit the other areas of the correctional facility.
Reading Wheels in prisons and their educational processes
Keywords: Educação não escolar em prisões; Leitura na prisão; Leitura e processos educativos; Non-school education in prisons; Reading in prison; Reading and educational processes; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO